Spatial distribution and ecological risks of polycyclic aromatic hydrocarbons in sea ice and seawater from northern Liaodong Bay, China. (January 2022) - Wu, Jinhao; Wang, Zhaohui; Zhang, Yufeng; Tian, Jiashen; Song, Lun; Han, Jiabo; Yu, Jianghua; Zhang, Yimin
Abstract: To better understand the spatial distribution and ecological risks of polycyclic aromatic hydrocarbons especially in low latitude coastal productive areas, PAHs in sea ice were examined for the first time in northern Liaodong bay of China in December 2020. Results showed ΣPAHs were dominated by 2- and 3-ring, with the mean concentration of 241.9 ng L −1 and 202.8 ng L −1 in sea ice and seawater, respectively, suggesting a moderate ecological risk based on Risk Quotients assessment. Ice enrichment factors were greater than 1 at 82% of the sampling sites, reflecting enrichment of PAHs in sea ice. The characteristic compounds ratios demonstrated PAHs mainly derived from petrogenic sources, while combustion was another crucial source for PAHs in sea ice via atmospheric deposition. This helps to better elucidate pollution status, potential sources and risk assessment of PAHs in productive coastal oceans especially during ice-covered period for contamination control and environmental management. Highlights: PAHs in sea ice were detected for the first time in the northern Liaodong bay. Most of the Ice Enrichment Factors of ΣPAHs were greater than 1. Pyrogenic activities were the main sources of PAHs in sea ice and seawater. RQ values of PAHs in sea ice and seawater indicated the moderate ecological risks.